Pamekasan’s Ghetak Mask Dance Movement in Ethnomathematics - Moh. Zayyadi; Yeyen Dwi Septiani (Universitas Islam Jember, 2023)
Ethnomathematics is one thing that is able to connect between culture and mathematics, which means that from a culture, steps are obtained to explore thinking skills that are able to produce various forms of mathematics. The study of ethnomathematics can be used as a learning resource for students to make it easier to learn mathematics. The purpose of ethnomathematics-based learning is to understand the relationship between mathematics and culture that is able to make students' and society's impressions of mathematics more meaningful. This study aims to determine the ethnomathematics in the Ghetak Pamekasan Mask dance movements. This research is a qualitative descriptive study with an ethnographic approach. In qualitative research, the data obtained by the researcher is written in the form of a narrative text to describe and produce a clear and detailed picture. The results of this study obtained a description of the ethnomathematics of the movement of the Ghetak Pamekasan mask dance in the mathematical concept of angular geometry. The mathematical concepts contained in the Ghetak Pamekasan Mask dance movements above can be used to introduce mathematics through local wisdom and abstract mathematical concepts will become concrete if they already know the mathematical concepts in the Ghetak Pamekasan Mask dance movements. Keywords: ethnomathematics; Ghetak Pamekasan Mask Dance Movement